2020
DOI: 10.1021/acs.jcim.9b01083
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Molecular Modeling Studies of Novel Coumarin Carboxamide Derivatives as eEF-2K Inhibitors

Abstract: Eukaryotic elongation factor-2 kinase (eEF-2K) is an unusual alpha kinase commonly upregulated in various human cancers, including breast, pancreatic, lung, and brain tumors. We have demonstrated that eEF-2K is relevant to poor prognosis and shorter patient survival in breast and lung cancers and validated it as a molecular target using genetic methods in related in vivo tumor models. Although several eEF-2K inhibitors have been published, none of them have shown to be potent and specific enough for translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…However, the three-dimensional structures of the catalytic domain of another α-kinase called myosin heavy-chain kinase A (MHCKA) is available and has been studied in considerable detail 35 . Therefore, we developed a predicted model of human eEF-2K used as a myosin heavy-chain kinase A (MHCK-A) template with homology modeling studies 36 . Next, we designed and screened different scaffolds of compounds including coumarin-chalcone scaffold and evaluated their activity by in silico using homology modeled target structure of eEF-2K.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the three-dimensional structures of the catalytic domain of another α-kinase called myosin heavy-chain kinase A (MHCKA) is available and has been studied in considerable detail 35 . Therefore, we developed a predicted model of human eEF-2K used as a myosin heavy-chain kinase A (MHCK-A) template with homology modeling studies 36 . Next, we designed and screened different scaffolds of compounds including coumarin-chalcone scaffold and evaluated their activity by in silico using homology modeled target structure of eEF-2K.…”
Section: Resultsmentioning
confidence: 99%
“…S1). In order to take into account, the flexibility of binding pocket residues of model protein 36 based on MHCK-A when the ligand approaches to the binding site, induced fit docking (IFD) method was considered. IFD results showed that 2C binds similar region identified by rigid docking, however, its binding pose was slightly different, as expected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations